Pengaruh Literasi Digital, Kecerdasan Intelektual, dan Kecerdasan Emosional Terhadap Kesiapan Kerja Mahasiswa Akuntansi - Nike Fatma; Viola Syukrina E Janrosl (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze and examine the effects of digital literacy, intelligence quotient (IQ), and emotional quotient (EQ) on the work readiness of accounting students in the era of Industry 4.0. The research employed a quantitative approach with an associative research design. The population consisted of all accounting students enrolled in higher education institutions in Batam City, with a sample of 327 respondents determined using the Slovin formula. Primary data were collected through online questionnaires using a Likert scale, supported by a literature review. Data analysis was conducted using Structural Equation Modeling (SEM) with the Partial Least Square (PLS) approach, processed through SmartPLS 4.0 software. The results indicate that digital literacy, intelligence quotient, and emotional quotient each have a positive and significant effect on the work readiness of accounting students. Among the three independent variables, digital literacy shows the most dominant influence, followed by emotional quotient and intelligence quotient. These findings suggest that work readiness is not solely determined by cognitive abilities, but also by digital competencies and emotional intelligence that are relevant to the demands of Industry 4.0. Therefore, higher education institutions are expected to integrate the development of digital literacy, intellectual intelligence, and emotional intelligence in a balanced manner to enhance the work readiness of accounting graduates.